Goffman at Penn: Star Presence, Teacher‐Mentor, Profaning Jester. Issue 1 (23rd December 2013) - Delaney, Michael
<x xml:space="preserve">Abstract</x> This essay is based on my encounters with Erving Goffman as his student at Penn in the 1970s. It concerns Goffman's largely self‐orchestrated "place" at Penn in various respects: his uneasy relationship with the Penn sociology department despite his academic fame; his disenchantment with "mainstream" sociology; his calibrated interactional style as a "profane jester, " offset by his thoughtful seriousness as a mentor; his classroom deportment and no‐nonsense teaching style. Goffman's casual classroom use of unseemly epithets is discussed as a pedagogical device for demonstrating the stigmatizing power of language. Goffman's suggestions for possible field‐site studies contrast with his commentary on the current state of sociology and, by implication, his place in it.